TAKHRIJ AL-HADIS (HADIS TENTANG WANITA HAID MASUK MASJID) - Nur khoridah Dalimunthe (Jurnal Payung Sekaki : Kajian Keislaman, 2025)
ABSTRACT The majority of Muslims in Indonesia prohibit women who are menstruating from entering the mosque. Based on the understanding of a hadith which states that the mosque is not halal for women who are menstruating. However, this view has begun to be challenged by various studies both in terms of law based on the evidence of the hadith and from a scientific perspective. This research is a literature study by referring to written data sources from books, hadith books, explanations of hadith, and journal articles. This research uses a comparative qualitative approach. The results of the study are that there are two hadith narrations about menstruating women entering the mosque, the first is the narration of Ibn Majah which prohibits women from entering the mosque which turns out to have the status of a weak hadith. The second is the hadith narrated by Abu Daud which allows women to enter the mosque as long as they do not dirty the mosque and keep dirt from falling into the mosque and its surroundings.